The Effects of Islamic Culture on the Occupational Performance of Clients Receiving Occupational Therapy in Islamic Countries: A Review Study With Content Analysis Approach - Hassan Vahidi; Nazila AkbarFahimi; Azad Rahmani; Mehdi Rassafiani (University of Social Welfare and Rehabilitation Sciences, 2023)
Objective One of the important factors in choosing purposeful activities and defining the occupational performance of people is the cultural context in the society, which may have different effects in the lives of clients in Islamic countries. This cultural structure in Islamic countries is largely influenced by the religious beliefs that govern the society. The effect of Islamic culture on the occupational performance of clients has been studied less. This study deals with the review of articles related to the relationship between the context of Islamic culture and the occupational performance of clients in Islamic countries using the explicit content analysis method. Therefore, the purpose of this study is to explain the effects of Islamic culture on the occupational performance of occupational therapy clients in Islamic countries. Materials & Methods The number of 46 studies using the keywords occupational therapy, Muslims and Islamic culture were initially selected until 2022 and the articles that were unrelated to occupational therapy and were not about Islam and Islamic culture were removed which finally reduced to 20 studies and then, they were subjected to qualitative analysis. Results The analysis of extractive studies has led to the emergence of different themes and categories, the theme of positive points has categories (importance of united family structure), (importance of religion in helping clients), (importance of pray as a purposeful activity) and theme challenges have categories (traditional treatments without clinical evidence), (importance of respecting the principle of Mahram in interpersonal communication), (specific beliefs in the cause of illness), (restrictions on praying), (cultural and local challenges), (hesitation in accepting occupational therapy philosophy). Conclusion In fact, Islam, with its influence on the family structure and the creation of positive beliefs and beliefs among the society, has been able to facilitate the process of occupational therapy and rehabilitation of clients to a great extent, but in the context of Islamic culture, there are many obstacles that unfortunately cause limitations. They are in interpersonal communication and acceptance of occupational therapy philosophy. Occupational therapists can use the opportunities to improve the client's performance, and in order to solve the challenges, it is necessary to do a lot of research to provide the necessary solutions.